Arc Andesitic Rocks Derived From Partial Melts of Mélange Diapir in Subduction Zones: Evidence From Whole‐Rock Geochemistry and Sr‐Nd‐Mo Isotopes of the Paleogene Linzizong Volcanic Succession in Southern Tibet. Issue 1 (30th January 2019) - Yan, Haoyu; Long, Xiaoping; Li, Jie; Wang, Qiang; Zhao, Bingshuang; Shu, Chutian; Gou, Longlong; Zuo, Rui
Abstract: Formation of andesitic rocks is crucial to understand the evolution of continental crust. Here we present an integrated study for the Paleocene Dianzhong Formation of the Linzizong volcanic succession (LVS) in the Lhasa terrane, southern Tibet. The andesites of the Dianzhong Formation have relatively high Mg # (38–60) and exhibit typical subduction‐like geochemical signatures. They are characterized by slightly enriched εNd (t) values (−2.82–0.35) and have a range of δ 98 / 95 Mo isotopic compositions (−0.40 to 0.13 ‰) larger than mid‐ocean ridge basalt. Their high Mg #, moderate light rare earth element‐enriched patterns, and slightly enriched εNd (t) values clearly rule out an origin of continental crust‐derived melts or partial melts of earlier underplated mafic rocks. The dacites show similar geochemistry to the andesites, indicating an origin from the parental magmas of the andesites. Based on the geochemical comparisons between the Dianzhong andesites and rocks of mélange, we suggest that the andesitic rocks of the LVS were derived from partial melts of a mantle source dominated by mélange that formed along the subduction channel. The mélange diapir melting was triggered by asthenospheric upwelling and corner flow during the Paleocene slab roll‐back of northward subducted Neotethyan oceanic crust. Because the Early Paleocene andesitic rocks in southern Lhasa show an average composition of continental crust, the partial melting of mélange rocks most likely provide an important mechanism for the production of andesitic magmas within continental arcs. Key Points: The Dianzhong andesites of the LVS were generated by partial melting of mélange rocks The Mo isotopic data support an input of subducted sediments into the magma source The mélange diapir melting was triggered by the roll‐back of northward subducted Neotethyan